Effects of Social Marketing Intervention on Physical Activity promotion Among the Elderly - Zahra Rohani; Reza Andam; Hasan Bahrololoum; Zhaleh Memari (Gonabad University of Medical Sciences, 2021)
Background: Social marketing emphasizes the use of commercial marketing concepts and their application for social purposes and also the change of voluntary behavior in a nonprofit manner. This study mainly aimed to examine the effectiveness of social marketing in changing the physical activity of the elderly. Besides, this study sought to determine the extent to which the Andreason social marketing criteria have been targeted in social marketing interventions. Methods: This was a narrative review study that investigated social marketing interventions to promote elderly physical activity, during 2000-2019. The scientific databases (Elmnet, SID, Irandoc, Civilica, Medline, ScienceDirect, Google Scholar, Web of Science, ProQuest, and Emerald) were searched between February and March 2019. The searched keywords included physical activity, social marketing, the elderly, social marketing mix, improving physical activity level, social marketing intervention, social marketing campaigns, and the Andreasen criteria. Finally, nine articles entered the study. Then, the mixed marketing components were extracted from the interventions, and six benchmarks of the Andrasen social marketing interventions were analyzed. Results: Most articles employed four components of the marketing mix. No intervention had applied the six measures of the Andrasen social marketing criteria. Also, five studies reported positive behavioral changes. However, other studies have reported no change in negative behavior. According to the evidence gathered in our study, social marketing offers an effective behavioral change approach to increase physical activity in the elderly. Conclusion: The present findings provide the basis for comprehensive and effective social marketing interventions.